Proof of concept for management of shoot blight and fire blight cankers on pear with preventive spray applications of giant knotweed extract - Borba, Matheus C.; Meredith, Christopher L.; Dhar, Bidhan C.; Aćimović, Srđan G. (Frontiers in Horticulture, 2023)
With the goal to develop management tools to mitigate the severity of shoot blight on pear caused by Erwinia amylovora and prevent fire blight canker development from infected shoots on pear tree wood, we evaluated five preventive treatments in inoculated experiments over 2-years. We focused on foliar spray and trunk injection applications of extract of giant knotweed, Reynoutria sachalinensis (RSE), as a plant resistance activator candidate and on comparisons to antibiotics. Five foliar applications of RSE (2.24 L/ha) on 3-year-old trees of cultivar ‘Bartlett’ resulted in 100% control of shoot blight severity and canker incidence in both years of evaluation. The RSE trunk injection in fall of the first year did not control the disease allowing 75% of shoot severity and 38.5% of canker incidence. The opposite happened in the second year where we injected RSE in spring, which provided 85.7% control of shoot blight severity and 89.8% control of canker incidence. Antibiotics oxytetracycline (OTC) and streptomycin (STM) did not provide consistent control in the first year in comparison to the second year. In the first year, both antibiotics, OTC (trunk injection and foliar spray) and STM were effective providing 94.8%, 100% and 86.3% control of shoot blight, respectively. They also provided 100, 91 and 84% control of canker incidence, respectively. However, in the second they were not effective allowing 69 – 96% of shoot blight severity and 70 – 92% of canker incidence. Regardless of the inconsistency in the effectiveness of antibiotics, which are not recommended for shoot blight control due to risks of promoting antibiotic resistance, five preventive spray applications of RSE could be used on pear trees to prevent shoot blight and canker development. Thus, the RSE spray program we developed could serve as a valuable control tool that could help prevent sudden outbreaks of shoot blight during summer and pear tree death from fire blight cankers with no risk for pathogen resistance.